Why China did not have a renaissance - and why that matters: an interdisciplinary dialogue - Maissen, Thomas; Mittler, Barbara (Critical readings in global intellectual history, 2018)
"This book takes the form of an interdisciplinary dialogue on periodization in global history. Focusing on the Renaissance, the aim is to question whether, when and how periodization schemes, which invariably reveal specific historical and cultural leanings, can fruitfully be applied outside of their "place of first occurrence." The analytical perspectives offered in the book are supplemented by readings from primary sources"--